MANAJEMEN LAYANAN PERPUSTAKAAN DI SMA NEGERI 1 DRAMAGA - Tuzahro, Siti Fatimah; Ihsan, Muzhir; Wibowo, Suryanto (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2023)
Management is the art of systematically influencing a group to carry out a series of activities through the processes of planning, directing, organizing, controlling, and implementing to achieve educational objectives. This research aims to describe the implementation of library service management at SMA Negeri 1 Dramaga. The method used is descriptive with a qualitative approach, and data collection was conducted through interviews, observations, and documentation. The subjects of the research are library staff who also serve as coordinators at SMA Negeri 1 Dramaga. The results indicate that the implementation of library service management at the school is still in the development stage but has started to progress well.